COMMONALITY IN THE USE OF PHILOSOPHICAL AND ENLIGHTENMENT TERMS IN AGAHI'S HISTORICAL AND LYRICAL WORKS (Scientific journal of the Fergana State University, 2023)
The article discusses the commonalities in the expression of philosophical and enlightenment worldview in the historical and lyrical works of Muhammad Riza Agahi, as well as the monotony of expression in the use of terms accordingly. The researcher also drew attention to the proportionality of the philosophical-enlightenment vocabulary in the prefaces of the historical works of the historian with the closeness of the philosophical-enlightenment worldview in the prefaces of Agahi’s “Tawizu-l-oshiqin” and historical works.